2015
DOI: 10.1186/s13075-015-0803-2
|View full text |Cite|
|
Sign up to set email alerts
|

Continuously elevated serum matrix metalloproteinase-3 for 3 ~ 6 months predict one-year radiographic progression in rheumatoid arthritis: a prospective cohort study

Abstract: IntroductionCore disease activity indicators of rheumatoid arthritis (RA) have been found to be limited in predicting joint destruction progression. Matrix metalloproteinase (MMP) 3 plays an essential role in joint destruction and was found elevated in some remission patients. We aimed to monitor dynamic core disease activity indicators and serum MMP-3 for one year and evaluate their value for predicting radiographic progression.MethodsPatients with active RA (Simplified disease activity index > 3.3) were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…In the current study, almost 47.2% of RA patients from Nantong China suffered from hand joint destruction. This prevalence estimate is significantly lower than those observed both in China [39] and other countries [5]. Such discrepancy could be explained that the majority of RA patients included in this study were outpatients with milder disease, which would have led to a lower prevalence estimate.…”
Section: Discussioncontrasting
confidence: 74%
“…In the current study, almost 47.2% of RA patients from Nantong China suffered from hand joint destruction. This prevalence estimate is significantly lower than those observed both in China [39] and other countries [5]. Such discrepancy could be explained that the majority of RA patients included in this study were outpatients with milder disease, which would have led to a lower prevalence estimate.…”
Section: Discussioncontrasting
confidence: 74%
“…A recent study demonstrated that low levels of MMP-3 at the onset of the disease predict a patient subgroup that exhibits no radiographic progression over 3-year methotrexate monotherapy and does not require combination therapy 32 . Another study found that continuously elevated serum MMP-3 may predict radiographic evidence of progression over 1 year in patients treated with various DMARDs using a treat-to-target protocol 33 . The above findings are also supported by those by Nawata et al demonstrating that high levels of MMP-3 predict a poor effect of infliximab and radiographic progression, especially in joint space narrowing, with high CRP levels being a negative prognostic factor for joint erosions.…”
Section: Resultsmentioning
confidence: 99%
“…25 Conventional radiographs of bilateral hands and wrists (anteroposterior view) were performed on all RA patients and assessed with the Sharp/van der Heijde modified Sharp score by two experienced observers (C. M. H. from radiology and M. J. D. from rheumatology) who were blinded to clinical data as we described previously. 26 Sixteen areas for joint erosion (JE) and 15 for joint space narrowing (JSN) of hands were assessed in each hand/wrist. The maximum score per single joint for JE is 5 and for JSN is 4, with the sum of JE (0-160) and JSN (0-120) subscores constituting total modified Sharp score (mTSS, 0-280).…”
Section: Clinical and Radiographic Assessmentmentioning
confidence: 99%